Designing fan charts for GDP growth forecasts to better reflect downturn risks - Turner, David (OECD Economics Department Working Papers, 2017)
Forecasts of GDP growth are typically over-optimistic for horizons beyond the current year, particularly because they fail to predict the occurrence or severity of future downturns. Macroeconomic forecasters have also long been under pressure to convey the uncertainty surrounding their forecasts, particularly since the financial crisis. The current paper proposes a method to address both these issues simultaneously by constructing fan charts which are parameterised on the basis of the historical forecasting track record, but distinguish between a "safe" regime and a "downturn-risk" regime. To identify the two regimes, use is made of recent OECD work on early warning indicators of a prospective downturn, relating to housing market or credit developments. Thus, when an early warning indicator is "flashing", the associated fan chart is not only wider to reflect increased uncertainty, but is also skewed to reflect greater downside risks using a two-piece normal distribution of the form used by central banks to provide fan charts around inflation forecasts. Conversely, in a safe regime, when the early warning indicators are not flashing, as well as being symmetric, the fan chart is narrower both relative to the downturn-risk regime and relative to what the fan chart would be if the dispersion was calculated with respect to the entire forecast track record with no distinction between regimes. The method is illustrated by reference to OECD GDP forecasts for the major seven economies made just prior to the global financial crisis, with fan charts calibrated using the track record of forecasts published in the OECD Economic Outlook. Fan charts which take account of early warning indicators in this way are much better at encapsulating the outturns associated with a downturn than a symmetrical fan chart calibrated indiscriminately on all forecast errors